Adiposity and glucose intolerance exacerbate components of metabolic syndrome in children consuming sugar‐sweetened beverages: QUALITY cohort study. Issue 4 (21st November 2012) - Wang, J. W.; Mark, S.; Henderson, M.; O'Loughlin, J.; Tremblay, A.; Wortman, J.; Paradis, G.; Gray‐Donald, K.
Summary: What is already known about this subject: The increase in sugar‐sweetened beverage (SSB) consumption over the last generation is temporally associated with epidemic levels of childhood obesity. There is increasing evidence linking added sugar consumption to the development of metabolic syndrome and type 2 diabetes. What this study adds: Higher SSB consumption is associated with elevated systolic blood pressure and greater insulin resistance among overweight/obese children whereas these associations are not evident among normal‐weight children. In youth with impaired glucose tolerance, higher SSB consumption is strongly associated with greater adiposity. Background: Sugar‐sweetened beverage (SSB) consumption is linked to weight gain and metabolic syndrome (MetS) components in children, but whether these associations are modified by excess weight and glucose tolerance status in children is not known. Objective: The objective of this study was to examine the cross‐sectional associations between SSB intake and MetS components among children above and below the 85th body mass index (BMI) percentile and those with and without impaired glucose tolerance (IGT). Methods: Data were from the QUébec Adiposity and Lifestyle InvesTigation in Youth study (2005–2008). Caucasian children aged 8–10 years (n = 632) were recruited from 1040 primary schools in Québec, Canada. SSB consumption was assessed by three 24‐h dietary recalls, body fat mass by dual‐energy absorptiometry, physical activity by 7‐d accelerometer. Multivariate linear regressions were used, with age, sex, fat mass index and physical activity as covariates, including waist circumference (WC), systolic blood pressure (SBP), concentrations of triglyceride and high‐density lipoprotein cholesterol and homeostasis model assessment of insulin resistance (HOMA‐IR) as outcome variables. Results: Among overweight children, a 100‐mL higher SSB consumption was associated with a 0.1‐unit higher HOMA‐IR ( P = 0.009) and a 1.1‐mm Hg higher SBP ( P = 0.001). In children with IGT, a 100‐mL higher SSB consumption was associated with a 1.4‐mm Hg higher SBP and a 4.0‐cm higher WC ( P < 0.001). These associations were not observed among children <85th BMI percentile. Conclusions: Our results suggest that the association between higher SSB consumption and MetS components is more evident in overweight/obese and glucose‐intolerant children.